The analysis of WIG20 stock index in R: a case study - Kotyra, B.; Krajka, A. (Математичне моделювання в економіці, 2014)
In this short note we would like to show the basic methods of analyzing time series. This methods leads us to the different models of time series (decomposition, ARIMA, Fourier techniques, exponentially smoothing and GARCH). The correctness of the models obtained may be verified by behavior of residuals (small variance, stationary, uncorrelated, normally distributes) or by verifying the predictions. This second method not will be discussed here. We omit the lot of data mining methods, which may be applied to the stock index time series, such as neural networks and genetic algorithms.